Plasmonic slot waveguides: a quantum leap in nonlinear nanophotonics - Rojas Yanez, Libertad; Hu, Huatian; Ciracì, Cristian; Palomba, Stefano (Frontiers in Nanotechnology, 2025)
Interest and excitement in nanophotonics—the study and control of light-matter interactions at the nanoscale—are driven by the ability to confine light to volumes well below a cubic wavelength, and, thereby, achieve extremely high intensities. This leads to light-matter interactions of unprecedented localization and strength. Such extreme behavior—both in terms of field enhancement and localization—can be achieved using plasmonic nanostructures, which concentrate light in regions much smaller than the wavelength of light, reducing the excitation power and, under certain conditions, removing phase-matching requirements in the nonlinear regime. In this study, we theoretically show that metal–dielectric–metal (MDM) slot waveguides (WGs), consisting of a thin dielectric layer sandwiched between metal films, provide the strongest confinement. We also demonstrate that integrating epsilon-near-zero (ENZ) materials within the MDM slot significantly improves the nonlinear conversion efficiency of these structures. The results show that the degenerate four-wave mixing conversion efficiency of these ENZ-MDM structures surpasses that of regular plasmonic structures and their dielectric counterparts, even under low pump power conditions, and remains robust despite higher losses in the ENZ material.